'Food is a Right … Nobody Should Be Starving on Our Streets': Perceptions of Food Bank Usage in a Mid-Sized City in Ontario, Canada. (18th March 2017) - Smith-Carrier, Tracy; Ross, Karen; Kirkham, Jennifer; Decker Pierce, Barbara
Abstract: The purpose of this exploratory descriptive qualitative study was to explore the experiences of people accessing the food bank in a mid-sized city in Ontario, Canada, and to gain their perspectives on more progressive alternatives to the charitable food bank model. We conducted interviews with 11 clients of the local food bank and two interviews with individuals experiencing food insecurity who do not access food banks (n = 13), and analysed these data using thematic analysis. Findings document participants' perceptions of the barriers to obtaining an adequate income, the key characteristics of and challenges associated with food banks, and proposed alternatives to the existing model. Using our study data, we document how the extant charitable food system engenders human rights violations; consider what would be required to move from a charitable model to a rights-based approach; and describe how food bank and human rights practitioners can promote a human rights framework in Canadian public policymaking. Through a rights-based framework, food provision moves beyond mere benevolence to positive rights; rights requiring legislative action and legal recourse should they be denied. In seeking alternatives to food banks, we conclude that a national strategy, built on a basic income and human rights framework, is needed. The perpetuation of food banks ensures the charitable food model is preserved, and people remain hungry.